2007
DOI: 10.1002/bjs.5492
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year follow-up of a randomized clinical trial comparing proton-pump inhibition with surgical therapy for reflux oesophagitis

Abstract: Chronic GORD can be treated effectively by either antireflux surgery or omeprazole therapy. After 7 years, surgery was more effective in controlling overall disease symptoms, but specific post-fundoplication complaints remained a problem. There appeared to be no dose escalation of omeprazole with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(86 citation statements)
references
References 41 publications
1
78
1
6
Order By: Relevance
“…Lundell and colleagues followed a cohort of 144 patients for 7 years after fundoplication examining for recurrence of GERD symptoms and the need to resume medical management of reflux symptoms. They found that 34% had symptomatic relapse, and many of them required medical management [15]. Smith and colleagues followed a cohort of 1892 patients for 10 years post fundoplication and found that 17% had resumed using antisecretory medications [16].…”
Section: Myth: Fundoplication Effectively Controls Reflux Symptomsmentioning
confidence: 99%
“…Lundell and colleagues followed a cohort of 144 patients for 7 years after fundoplication examining for recurrence of GERD symptoms and the need to resume medical management of reflux symptoms. They found that 34% had symptomatic relapse, and many of them required medical management [15]. Smith and colleagues followed a cohort of 1892 patients for 10 years post fundoplication and found that 17% had resumed using antisecretory medications [16].…”
Section: Myth: Fundoplication Effectively Controls Reflux Symptomsmentioning
confidence: 99%
“…As a result, laparoscopic antireflux surgery (LARS) has become the gold standard in the surgical treatment of GORD. Lundell et al 2 reported a 7-year follow-up comparing results in patients randomised to proton-pump inhibition or open antireflux surgery, and surgery was shown to be more effective at controlling overall disease symptoms, but post-fundoplication complaints were problematic.…”
mentioning
confidence: 99%
“…The two treatments were similar regarding the incidence of recurrent esophagitis (10.3% omeprazole versus 11.8% antireflux surgery). In addition the two therapies appeared to be equivalent in healing esophageal mucosa (Lundell et al 2007). Another randomized trial, with 10 year follow-up, evaluating the effectiveness of medical therapy (omeprazole) versus antireflux surgery found that patients who underwent surgery had improved symptoms' relief when compared to the medically treated group (Spechler et al 2001).…”
Section: Surgerymentioning
confidence: 99%